2019
DOI: 10.1080/10428194.2019.1658102
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone, oxaliplatin and cytarabine (R-DHAOx) as salvage and stem cells mobilizing therapy in relapsed/refractory diffuse large B cell lymphomas

Abstract: Cisplatin-containing salvage regimens followed by autologous hematopoietic stem cell (HSC) transplantation are the current standard of care for relapsed or refractory (R/R) lymphomas. We retrospectively analyzed efficacy and stem cell mobilizing activity of oxaliplatin, cytarabine, dexamethasone and rituximab (R-DHAOX) in 53 R/R diffuse large B cell lymphomas (DLBCL) treated in our centre (median lines 2, range 2-5; median age 59, range 22-79). Hematological toxicity was manageable and no patients experienced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…We found that, out of 19 patients that underwent the mobilization procedure, 18 achieved an adequate number of CD34 + cells for ASCT. Only 1 patient (5%) failed mobilization, which was the identical rate observed in historical results with the R‐DHAP regimen 24 . No patients required plerixafor, an antagonist of the alfa chemokine receptor, CXCR4.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We found that, out of 19 patients that underwent the mobilization procedure, 18 achieved an adequate number of CD34 + cells for ASCT. Only 1 patient (5%) failed mobilization, which was the identical rate observed in historical results with the R‐DHAP regimen 24 . No patients required plerixafor, an antagonist of the alfa chemokine receptor, CXCR4.…”
Section: Discussionsupporting
confidence: 67%
“…Only 1 patient (5%) failed mobilization, which was the identical rate observed in historical results with the R-DHAP regimen. 24 No patients required plerixafor, an antagonist of the alfa chemokine receptor, CXCR4. The average number of CD34 + cells collected was 5.525 � 10 6 /kg, which was sufficient for transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In the relapsed setting, patients also usually need immediate salvage. Outpatient regimens such as gemcitabine-based regimens, with rituximab, gemcitabine, cisplatin and dexamethasone (R-GDP), 13 or oxaliplatin-based, with rituximab, dexamethasone, cytarabine and oxaliplatin (R-DHAOX), 14 should be considered. The autologous stem-cell transplant (ASCT) should not be delayed, except in critical cases, due to the risk of progression and the need for more treatment.…”
Section: Aggressive B-cell Lymphomasmentioning
confidence: 99%
“…The patient was immediately started on the salvation protocol R-DHAOX (rituximab dexamethasone cytarabine oxaliplatin) [15] but died of septic shock 10 months after the initial presentation and after the fourth cycle of the second-line chemotherapy.…”
Section: Case Presentationmentioning
confidence: 99%